Comparison of The Mechanical Properties and Drilling Performance of The AISI 316 Parts Produced with Casting, LPBF and WAAM - Kocaman, Engin; Köklü, Uğur; Morkavuk, Sezer; Coşkun, Mert; Koçar, Oğuz; Dilibal, Savaş; Gürol, Uğur (Springer, 2024)
AISI 316 stainless steel parts are widely utilized in many industrial fields with a vast scope of applications. These steel parts, which are used in many fields, can be produced using different production methods, but the mechanical properties of the parts produced with different processes may be different, and the machinability characteristics will also be different. In this study, the drilling machinability characteristics of AISI 316 stainless steel parts manufactured via cast, LPBF and WAAM methods were experimentally investigated and compared considering thrust force generation, burr analysis and chip morphology. In order to clarify the differences in machinability behavior among the tested samples, the corresponding microstructure, microhardness and mechanical strength (yield strength, UTS and elongation) were also examined in detail. The experimental results showed the manufacturing method, and particularly cooling rate, significantly affecting the microstructure, mechanical response and further machinability characteristics; besides, due to higher cutting forces generation, the machinability of the parts produced by additive manufacturing methods (LPBF and WAAM) is more difficult compared to the parts produced by conventional manufacturing methods (cast and cast-HT).
Keywords: Laser Powder Bed Fusion (LPBF); Wire Arc Additive Manufacturing (WAAM); Casting; AISI 316; Drilling